A diverse group of echogenic particles observed with a broadband, high frequency echosounder. (18th September 2017) - Briseño-Avena, Christian; Franks, Peter J S; Roberts, Paul L D; Jaffe, Jules S; ,
Abstract: In 1980, Holliday and Pieper stated: "Most sound scattering in the ocean volume can be traced to a biotic origin." However, most of the bioacoustics research in the past three decades has focused on only a few groups of organisms. Targets such as small gelatinous organisms, marine snow, and phytoplankton, e.g. have been generally to be considered relatively transparent to acoustic waves due to their sizes and relatively low sound speed and density contrasts relative to seawater. However, using a broadband system (ZOOPS-O 2 ) we found that these targets contributed significantly to acoustic returns in the 1.5–2.5 MHz frequency range. Given that phytoplankton and marine snow layers are ubiquitous features of coastal regions; this works suggests that they should be considered as potential sources of backscatter in biological acoustic surveys.